Type-specific impacts of silver on the protein profile of tomato (Lycopersicon esculentum L.). Issue 1 (2nd January 2022) - Noori, Azam; Bharath, Leena P.; White, Jason C.
Abstract: Silver nanoparticles (AgNPs) are particularly among the widely used nanomaterials in medicine, industry, and agriculture. The small size and large surface area of AgNPs and other nanomaterials result in their high reactivity in biological systems. To better understand the effects of AgNPs on plants at the molecular level, tomato ( Lycopersicon esculentum L. ) seedlings were exposed to 30 mg/L silver in the form of nanoparticle (AgNPs), ionic (AgNO3 ), or bulk (Ag 0 ) in 50% Hoagland media for 7 days. The effects of silver on the expression of plant membrane transporters H + -ATPase, vacuolar type H + -ATPase (V-ATPase), and enzymes isocitrate dehydrogenase (IDH), and catalase in roots was assessed using RT-qPCR and immunofluorescence-confocal microscopy. We observed significantly higher expression of catalase in plants exposed to AgNPs (Fold of expression 1.1) and AgNO3 (Fold of expression 1.2) than the control group. The immunofluorescence imaging of the proteins confirmed the gene expression data; the expression of the enzyme catalase was upregulated 41, 216, and 770% higher than the control group in plants exposed to AgNPs, Ag 0, and AgNO3, respectively. Exposure to AgnO3 resulted in the upregulation (fold of expression 1.2) of H + -ATPase and downregulation (fold of expression 0.7) of V-ATPase. A significant reduction in the expression of the redox-sensitive tricarboxylic cycle (TCA) enzyme mitochondrial IDH was observed in plants exposed to AgNPs (38%), AgNO3 (48%), or Ag 0 (77%) compared to the control. This study shows that exposure to silver affects the expression of genes and protein involved in membrane transportation and oxidative response. The ionic form of silver had the most significant effect on the expression of genes and proteins compared to other forms of silver. The results from this study improve our understanding about the molecular effects of different forms of silver on important crop species. Novelty statement Silver nanoparticles released into the environment can be oxidized and be transformed into ionic form. Both the particulate and ionic forms of silver can be taken by plants and affect plants physiological and molecular responses. Despite the extensive research in this area, there is a scarce of information about the effects of silver nanoparticles on the expression of membrane transporters especially H + -ATPase involved in regulating cells' electrochemical charge, and the activity of enzymes involved in oxidative stress responses. This is a unique study that evaluates the expression of cellular proton transporters and enzymes of redox balance and energy metabolisms such as membrane transporters, H + -ATPase, and V-ATPases, and enzymes catalase and IDH. The results provide us valuable information about the impact of silver on plants at the molecular level by evaluating the expression of genes and proteins. Key Message: The exposure of plants to silver as an environmental stressor affects the expression of genes and proteins involved in maintaining cell's electrochemical gradient (H + -ATPase, V-ATPase) and redox potential (IDH, catalase). Graphical Abstract: UF0001